Improving The Performance of Sales Employees Through Workload and Work Motivation at PT. X - Maria Sonya Meidika P; Dian Lestari (CV. Syntax Corporation Indonesia, 2024)
The purpose of this study is to determine how the workload and work motivation of employees on the performance of PT X employees and determine the effect both partially and simultaneously. This study used quantitative associative analysis which was used to determine the influence of the independent variable with the dependent variable. The sample of this study used a saturated sample of 57 employees of PT X sales department with data collection techniques in the form of interviews, questionnaires, and documentation. The data analysis technique used is multiple linear regression with SPSS 27 software. The results showed that partially workload had a negative effect on employee performance and work motivation had a positive effect on employee performance. Simultaneously, workload and work motivation affect employee performance.